Hubungan Fungsi Seksual dengan Kecemasan Pasien Pasca-Infark Miokard Akut - Melinda Harini; Deddy Tedjasukmana; Tresia Fransiska U Tambunan; Muhammad Yamin; Petrin Redayani Lukman S; Hamzah Shatri; Melinda Harini (The Indonesian Heart Association, 2016)
Background: Sexual dysfunction and anxiety frequently happens on patients after acute myocardial infarction (AMI) and can affect patients’ quality of life. The purpose of this study was to examine the assosiation of sexual function post-AMI patients with anxiety. Methods: It was a cross-sectional study. Respondents are patients in Integrated Cardiac Clinic of Cipto Mangunkusumo Hospital that meet inclusion and exclusion criteria. They signed informed consent. Sexual function was assessed using International Index of Erectyle Function (IIEF) and anxiety was assessed using Hamilton Anxiety Rating Scale (HAM-A). Results: Post-AMI patients had erectile dysfunction (82.5%), orgasm dysfunction (72.5%) and libido dysfunction (93.8%). Respondents expressed sexual intercourse dissatisfaction (97.5%) and overall dissatisfaction (90%). The proportion of post-AMI anxiety was 52.5%. There was no assosiation between sexual function post-AMI with anxiety. Conclusion: Anxiety and sexual dysfunction post-AMI is a considerable problem. Factors that affect anxiety and sexual dysfunction post-AMI needs to be explored further so that an integrated management guidelines could be proposed.